Career Success Criteria Clarity as a Predictor of Employment Outcomes - Xin, Lu; Zhou, Wenxia; Li, Mengyi; Tang, Fangcheng (Frontiers in Psychology, 2020)
Drawing on goal setting theory and social cognition career theory, this study empirically proposes an operational definition of career success criteria clarity (CSCC) and further explores its impact on career satisfaction, person-job fit, and subjective well-being through the mediating role of career decision-making self-efficacy (CDSE). A pilot study of 231 samples showed that the CSCC scale had good reliability and validity. To further test the effects of CSCC on crucial employment outcomes, as well as the mediating role of CDSE, 240 employees were included in an additional survey. Structural equation modeling path analysis supported all the expected hypotheses. Results indicated that: 1) CSCC was positively correlated to career satisfaction; 2) CSCC was positively correlated to person-job fit; 3) CSCC was positively correlated to subjective well-being; 4) CSCC was positively correlated to CDSE; 5) CDSE fully mediated the relationship between CSCC and career satisfaction; 6) CDSE fully mediated the relationship between CSCC and person-job fit; and 7) CDSE partly mediated the relationship between CSCC and subjective well-being. The results contributed to social cognition career theory model and provided suggestions for both the career educators and consultants.